Manejo poscosecha de granadilla en la parroquia Yangana, cantón y provincia de Loja - Puga Muima, Adriana Maribel (2021)
The importance of preserving fruit quality and safety allows for reduction of post-harvest losses and ensure product sales, however, there are limitations in the development of these processes. The present study aims to contribute to the socioeconomic development of producers through the improvement of passion fruit post-harvest handling techniques in the Yangana parish, in the Loja canton and province, in this context, a post-harvest diagnosis was made to the producers through survey applying, from this, inconveniences were identified in some stages, which were considered for the research development, for this, preliminary tests were carried out with different package and disinfectant types (20 ppm sodium hypchlorite, 40 ppm ozone and 100 ppm acetic acid), also, these treatments were stored at 7 and 10 °C temperatures to finally develop organoleptic, physical-chemical and microbiological analysis; based on the quality analysis results, definitive treatments were determined, were it is considered that passion fruit must be harvested in a 5 maturity state, disinfected with 20 ppm sodium hypochlorite for 2 min., packed in cardboard boxes and refrigerate at 7 °C, shelf life corresponds to 40 days; whose variable production cost and public sale price were of 0,20 and 0,25 USD. KEYWORDS: Post-Harvest, Passion fruit, Quality and Disinfection.